2009
DOI: 10.1097/01.won.0000347660.87346.ed
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Wound-Associated Pain and Healing Trajectory With a Comprehensive Foot and Leg Ulcer Care Model

Abstract: A comprehensive patient assessment can improve chronic leg and foot ulcer wound-related pain and healing rates. The mean pain scores are lower for patients with healed ulcers than for those who do not obtain complete wound closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
(40 reference statements)
4
37
1
Order By: Relevance
“…In our study, patients with smaller injuries had lower pain intensity and lower pain impact on quality of life. A study comparing pain intensity in patients with healed and open ulcers has shown that patients with healed ulcers had lower pain intensity 15 , thus confirming our findings. Our study has found association between VU-related pain and aspects of assistance and of the injury, which suggests that interventions focused on such factors could contribute to control those patients' pain.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our study, patients with smaller injuries had lower pain intensity and lower pain impact on quality of life. A study comparing pain intensity in patients with healed and open ulcers has shown that patients with healed ulcers had lower pain intensity 15 , thus confirming our findings. Our study has found association between VU-related pain and aspects of assistance and of the injury, which suggests that interventions focused on such factors could contribute to control those patients' pain.…”
Section: Discussionsupporting
confidence: 82%
“…This hypothesis, however, should be tested in future studies. Effective pain control brings unquestionable benefits to the quality of life of VU patients and there is a study indicating that adequate pain control also contributes to ulcer healing, which should also be tested in future studies 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain stimulates the release of inflammatory mediators that interfere with repair tissue [21] and, when severe, it can be related to local infection, increasing healing time.…”
Section: Sociodemographic Clinical and Care Influence In The Healinmentioning
confidence: 99%